2015
DOI: 10.5194/tc-9-123-2015
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the transfer of supraglacial meltwater to the bed of Leverett Glacier, Southwest Greenland

Abstract: Abstract. Meltwater delivered to the bed of the GreenlandIce Sheet is a driver of variable ice-motion through changes in effective pressure and enhanced basal lubrication. Ice surface velocities have been shown to respond rapidly both to meltwater production at the surface and to drainage of supraglacial lakes, suggesting efficient transfer of meltwater from the supraglacial to subglacial hydrological systems. Although considerable effort is currently being directed towards improved modelling of the controllin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(109 citation statements)
references
References 51 publications
6
99
1
Order By: Relevance
“…The presence of crevasses is dependent on the stress regime within the ice, and recent modelling studies in Greenland have used the von Mises yield criterion [44,46] to predict areas where crevassing will occur. Where crevasses intersect surface drainage, meltwater ponding in the crevasse will occur establishing the potential for hydrofracture to propagate the crevasse to the glacier bed [48].…”
Section: Englacial Meltwater Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of crevasses is dependent on the stress regime within the ice, and recent modelling studies in Greenland have used the von Mises yield criterion [44,46] to predict areas where crevassing will occur. Where crevasses intersect surface drainage, meltwater ponding in the crevasse will occur establishing the potential for hydrofracture to propagate the crevasse to the glacier bed [48].…”
Section: Englacial Meltwater Processesmentioning
confidence: 99%
“…Rapid lake drainage results in large volumes of water entering the subglacial drainage system in a few hours with rates of 8700 and 3300 m 3 s −1 recorded [9,41]. In order for surface lakes to drain, an appropriate stress regime in the ice is required with existing crevasses, which can then be exploited and expanded by ponded surface waters draining englacially via hydrofracture [46][47][48]. There is as yet no evidence however to support the idea of a unifying critical lake volume or depthdependent drainage threshold [38].…”
Section: Supraglacial Meltwater Processesmentioning
confidence: 99%
“…Surface crevasses provide one mechanism facilitating meltwater transport. It has been suggested that conditions promoting crevasse formation are limited to below ∌1400 m (Clason et al, 2015) to 1600 m elevation (Poinar et al, 2015) in the study area. Meltwater-induced seasonal variations in ice motion have been observed to elevations reaching ∌1500-1600 m (Bartholomew et al, 2011;Palmer et al, 2011).…”
Section: Enhanced Basal Slipmentioning
confidence: 99%
“…Mean winter velocities for [2008][2009] are provided at 500 m resolution by the MEaSUREs Greenland Ice Sheet Velocity Map dataset (Joughin et al, 2010a, b). For the inversion procedure, the winter velocities, along with their associated errors, are reinterpolated to 1000 m. Velocities at 500 m resolution are used to determine surface stresses, assuming an ice temperature of −5 ‱ C. Crevassed areas are then calculated using a von Mises stress criterion following Clason et al (2015). A crevassing threshold is selected by comparing the von Mises stress to observed patterns of crevassing in a Landsat 8 image, acquired on 19 August 2013.…”
Section: Study Area and Datasetsmentioning
confidence: 99%